Efforts to Improve Mathematics Learning Outcomes through The Implementation of PBL Model on SPLDV Material - Arinda Pratini; Maimunah Maimunah; Syarifah Nur Siregar (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
This classroom action research aims to improve learning outcomes of students through the implementation of the problem-based learning model. This research was carried out at the VIII1 class of SMP Negeri 3 Pekanbaru in academic year 2019/2020 on the material of two-variable linear equation systems (SPLDV). The subjects were 39 students consisting of 18 male and 21 female students with heterogenous academic ability. This research was conducted within 2 cycles, namely; the first cycle consisted of two meetings and the second cycle consisted of three meetings. The instruments of this research were learning medias consisting of syllabus, student’s worksheet, as well as the data collection instruments consisting of teacher and students’ activities sheet and students learning outcomes sheets. According to the results of the analysis of the teacher and student activity data, it shows that there is an improvement in each meeting after the implementation of the PBL model. Student mathematics learning outcomes data on knowledge and skill competencies also indicate an increase in the percentage of students with learning outcomes equal to or more than 75 in accordance with the established minimum passing criteria. The results of this study specify that the implementation of the PBL model is able to improve students learning outcomes of class VIII1 students of SMP Negeri 3 Pekanbaru for the 2019/2020 academic year on SPLDV material.